Digital Transformation in Waste Management: A Study of the Digital Waste Bank Program in Bojonegoro - Lestari, Maya Puji; Taufiq, Ahmad; Rupiarsieh (Universitas Medan Area, 2025)
This study aims to analyze digital transformation in waste management in Bojonegoro Regency. This study uses a descriptive qualitative method with data collection techniques through literature studies, observations, and interviews. This research is based on the Royyana Theory, which involves five indicators, namely human resources, processes, strategies, structures, and technology as tools to improve performance. The study results show that implementing digital waste banks in Bojonegoro Regency has fulfilled essential aspects of digital transformation. Competent human resources can run the program effectively; the service process is carried out optimally to support work efficiency; digitalization socialization strategies to the community have proven to be efficient and easy to understand; the management structure of the digital waste bank is running well; and the integration of technology has made it easier for people to make transactions digitally. The significance of the results of this study lies in the real positive impact, namely increasing public awareness and participation in digital-based waste management, which ultimately contributes to environmental sustainability. This research shows that digital waste banks can be a relevant innovation model for other regions in supporting digital transformation for ecological management.